CONSTRUCTING COHERENT IDEAS AND USING COHERENCE DEVICES IN WRITTEN DESCRIPTIVE ESSAYS: A Study at the Fourth Grade English Department Students of STBA Haji Agus Salim Bukittinggi - Nopita, Dewi (English Department FBS UNP, 2011)
This paper derived from the research results conducted in 2011, looks into the skill of the fourth grade English department students of STBA Haji Agus Salim Bukittinggi in constructing coherent ideas and in using coherence devices in writing descriptive essays. The students’ skill in constructing coherent ideas concerned the relevance and the order of ideas and in using coherence devices concerned the repetitions of the key words/nouns and the use of pronouns and transitional signals. The research results show that the students had weak skill in constructing coherent ideas and had low average skill in using the coherence devices. In relation to constructing coherent ideas, the relevance and the order of ideas of the students’ descriptive essays were weak. Then, in relation to the use of coherence devices, the students’ skill in repeating the key words/nouns was weak, and in using pronouns and transitional signals were high average. Therefore, the students could not achieve coherence in writing descriptive essays yet. Key words/phrases: writing descriptive essays, coherent ideas, coherence devices